Relevance of Invasive Testing in Era of Non-Invasive Testing for Prenatal Chromosomal Abnormalities - Abhijeet Kumar; Madhusudan Dey; Devendra Arora (Gynecology Obstetrics & Reproductive Medicine)
Prenatal screening for chromosomal abnormalities has two components i.e. prenatal screening (maternal serum screening and cell-free fetal DNA screening) and prenatal diagnosis (chorionic villus sampling, amniocentesis, and cordocentesis). Prenatal testing in the past decade is evolving towards non-invasive methods to determine the chromosome abnormality disorders in the fetus without incurring the risk of miscarriage. Conventional tools for prenatal screening included maternal age, maternal serum markers, ultrasound marker (nuchal thickness), and their combinations. With the increased risk of screening test patients were offered diagnostic tests (chorionic villus sampling, amniocentesis, and cordocentesis). After the availability of noninvasive prenatal tests for commercial use in 2011, a great marketing drive is there to establish it as a master tool for prenatal testing. However various society guidelines i.e. ACOG, RCOG, and ISUOG have clearly stated that cell-free fetal DNA based noninvasive prenatal tests is a screening test, not a diagnostic test. In the succeeding paragraph, we will review current trends in the field of cell-free fetal DNA noninvasive prenatal tests and the relevance of invasive testing in the context of noninvasive prenatal tests. Noninvasive prenatal tests does not entirely replace invasive prenatal testing procedures. Positive noninvasive prenatal tests findings must be confirmed by diagnostic tests based on an invasive sample source, mainly chorionic villus sampling or amniocentesis due to false positive and false negative reports of cell-free fetal DNA based tests. Continuing research and development efforts are focused on overriding noninvasive prenatal tests limitations. Recent studies show that procedure-associated risks in the case of prenatal invasive testing are very low as compared to previous studies. Prenatal invasive testing will remain as the backbone of prenatal diagnostic testing until the limitation of noninvasive prenatal tests is overcome.